TRANSTENSIONAL MECHANISM ANALYSIS OF FORKLIFT TRANSMISSION WHEEL HUB STUD - SUI ZhiJun; FENG ZhiHua; ZHANG ZhiYong (Jixie qiangdu)
By mechanical analysis to analyze the mechanism of wheel hub stud rotating and transtensional when taking strenuous test to forklift transmission,if pre-tightening force between rim and wheel hub is not enough because of the unqualified nut,Ground braking force is more than friction force when truck brakes,rim rotates to the brake drum and nut,wheel hub stud bears extra twisting force between rim and nut,causing wheel hub stud rotating and transtesional. Learning the mechanism of wheel hub stud rotating and transtensional is helpful to know further the wheel hub stud working force condition,and it can give theoretical basis to the failure analysis of wheel hub stud and nut